Swallowing tablets and capsules increases the risk of penetration and aspiration in patients with stroke-induced dysphagia - Schiele, Julia T.; Penner, Heike; Schneider, Hendrik; Quinzler, Renate; Reich, Gabriele; Wezler, Nikolai; Micol, William; Oster, Peter; Haefeli, Walter E. (Dysphagia, 2015)
We evaluated the prevalence of difficulties swallowing solid dosage forms in patients with stroke-induced dysphagia and whether swallowing tablets/capsules increases their risk of penetration and aspiration. Concurrently, we explored whether routinely performed assessment tests help identify patients at risk. Using video endoscopy, we evaluated how 52 patients swallowed four different placebos (round, oval, and oblong tablets and a capsule) with texture-modified water (TMW, pudding consistency) and milk and rated their swallowing performance according to the Penetration Aspiration Scale (PAS). Additionally, Daniels Test, Bogenhausener Dysphagiescore, Scandinavian Stroke Scale, Barthel Index, and Tinetti’s Mobility Test were conducted. A substantial proportion of the patients experienced severe difficulties swallowing solid oral dosage forms (TMW: 40.4 %, milk: 43.5 %). Compared to the administration of TMW/milk alone, the placebos increased the PAS values in the majority of the patients (TMW: median PAS from 1.5 to 2.0; milk: median PAS from 1.5 to 2.5, each p value <0.0001) and residue values were significantly higher (p < 0.05). Whereas video-endoscopic examination reliably identified patients with difficulties swallowing medication, neither patients’ self-evaluation nor one of the routinely performed bedside tests did. Therefore, before video-endoscopic evaluation, many drugs were modified unnecessarily and 20.8 % of these were crushed inadequately, although switching to another dosage form or drug would have been possible. Hence, safety and effectiveness of swallowing tablets and capsules should be evaluated routinely in video-endoscopic examinations, tablets/capsules should rather be provided with TMW than with milk, and the appropriateness of “non per os except medication” orders for dysphagic stroke patients should be questioned.
Gesehen am 24.06.2020